2001
DOI: 10.1111/j.1469-7793.2001.0167m.x
|View full text |Cite
|
Sign up to set email alerts
|

Soleus H‐reflex gain in humans walking and running under simulated reduced gravity

Abstract: The Hoffmann (H-) reflex is an electrical analogue of the monosynaptic stretch reflex, elicitedby bypassing the muscle spindle and directly stimulating the afferent nerve. Studying H-reflex modulation provides insight into how the nervous system centrally modulates stretch reflex responses.2. A common measure of H-reflex gain is the slope of the relationship between H-reflex amplitude and EMG amplitude. To examine soleus H-reflex gain across a range of EMG levels during human locomotion, we used simulated redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
83
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 52 publications
11
83
1
3
Order By: Relevance
“…This suggests that the increases in EMG amplitude during limb loading were not caused by stretch reflex activation. Previous studies have found that the EMG amplitude increases in proportion to lower limb loading in nondisabled and spinal cord-injured humans, 4,[16][17][18] but those studies have examined normal bilateral stepping where the limb undergoes considerable flexion and extension with each step.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the increases in EMG amplitude during limb loading were not caused by stretch reflex activation. Previous studies have found that the EMG amplitude increases in proportion to lower limb loading in nondisabled and spinal cord-injured humans, 4,[16][17][18] but those studies have examined normal bilateral stepping where the limb undergoes considerable flexion and extension with each step.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that the soleus H-reflex amplitude decreases with increasing walking speeds (17)(18)(19)(20). However, it is not known if the soleus H-reflexes decrease with an increase in walking speed in patients after SCI.…”
Section: Introductionmentioning
confidence: 93%
“…Afferent input from step to step may also vary within a given bin. Given that H reflex amplitudes have been shown to be modulated by both phasedependent muscle activation levels during ambulation [2,[5][6][7][8] and by ankle [9][10] and hip joint positions [11,29], precisely stimulating sequential H reflex cycles during the gait cycle may reduce variability in modulation factors that affect H reflex output. Robotic-controlled BWSTT provides highly repeatable gait characteristics that would be difficult to control during therapist-assisted BWSTT.…”
Section: Discussionmentioning
confidence: 99%
“…Methods include selecting a constant percentage of the M max to be maintained across conditions. Investigators have used intensities ranging from 10 to 30 percent [7,[30][31][32][33], multiple stimulation intensities with post hoc analysis to match M wave cycles [2,6], or have not reported. Acceptable M wave variance for these studies was between ±3 to 5 percent of selected intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation